Epidemiology and outcome of invasive fungal disease in children after hematopoietic cell transplantation or treated for malignancy: Impact of national programme of antifungal prophylaxis. Issue 11 (21st October 2019) - Czyżewski, Krzysztof; Gałązka, Przemysław; Frączkiewicz, Jowita; Salamonowicz, Małgorzata; Szmydki‐Baran, Anna; Zając‐Spychała, Olga; Gryniewicz‐Kwiatkowska, Olga; Zalas‐Więcek, Patrycja; Chełmecka‐Wiktorczyk, Liliana; Irga‐Jaworska, Ninela; Bień, Ewa; Ociepa, Tomasz; et al.
Summary: The objective of the study was the analysis of incidence and outcome of invasive fungal disease (IFD) in children treated for malignancy (PHO, paediatric hematology‐oncology) or undergoing hematopoietic cell transplantation (HCT) over a period of six consecutive years in nationwide study. A total number of 5628 patients with newly diagnosed malignancies and 971 patients after HCT (741 allo‐HCT and 230 auto‐HCT) were screened for infectious complications in biennial reports. IFD incidence was lower among PHO patients: 8.8% vs 21.2% ( P < .0001) and survival from IFD was better: 94.2% vs 84.1% ( P < .0001). Auto‐HCT patients had lower incidence (10.9% vs 24.4%) and lower mortality than allo‐HCT patients. Introduction of national antifungal prophylaxis programme in HCT and acute leukaemia patients decreased incidence of IFD in HCT (from 23.1% to 13.4%) and AML on conventional chemotherapy (from 36% to 23%) but not in ALL patients during chemotherapy. In multivariate analysis, the incidence of IFD was higher in patients after HCT, diagnosed for ALL, AML or NHL, and in patients > 10 years old. Factors contributing to death with infection were as follows: undergoing HCT, diagnosis of acute leukaemia (ALL or AML) and duration of treatment of infection > 21 days. In conclusion, the incidence of IFD in allo‐HCT and in AML patients on chemotherapy has decreased after introduction of national programme of antifungal prophylaxis, while the incidence of IFD in ALL patients on chemotherapy did not change significantly. The outcome of IFD both in PHO and HCT patients has largely improved in comparison with historical international data.